Local Fractional Series Expansion Method for Solving Wave and Diffusion Equations on Cantor Sets - Ai-Min Yang; Xiao-Jun Yang; Zheng-Biao Li (Abstract and Applied Analysis)
We proposed a local fractional series expansion method to solve the wave and diffusion equations on Cantor sets. Some examples are given to illustrate the efficiency and accuracy of the proposed method to obtain analytical solutions to differential equations within the local fractional derivatives.